THROUGH A MICROSCOPIC LENS: SKIN MICROBIOME AS THE CONFEDERATE IN ATOPIC DERMATITIS - Catharina Clarissa Ursia; Patricia Dian Putri (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Reciprocity between skin microbiome and the host underlies the occurrence, exacerbation, and severity of atopic dermatitis (AD). However, the role of skin microbiome in the pathogenesis of AD is yet to be depicted. This review highlights the host–microbiome interactions which relies on barrier status, microbiome composition, and microbe–microbe interactions. A microbiome shift, with abundance of S. aureus and lower microbial diversity, compromises the skin barrier function. It goes to show that epidermal barrier defect depletes the protective commensal skin bacteria and demonstrate how dysbiosis of the skin microbiome can lead to AD.